The Influence Of Economic Digitalization On The Productivity Of Micro, Small, And Medium Enterprises (MSMES) In Palopo City - Nurul citra pratiwi; Antong; Muh Yusuf Q (LP2M IAIN Palopo, 2026)
This study aims to analyze the influence of economic digitalization on the productivity of Micro, Small, and Medium Enterprises (MSMEs) in Palopo City. Digitalization includes the use of digital platforms.e-commerceand social media play a vital role in improving operational efficiency and expanding the market reach of MSMEs. Using quantitative methods and questionnaire data collection, this study involved 80 MSME respondents in Palopo. The analysis showed that the use of social media platformse-commerceand social media have a significant positive impact on MSME productivity. Furthermore, MSMEs that adopt digital technology have recorded increased turnover and operational efficiency, despite still facing obstacles such as low digital literacy and inadequate technological infrastructure. limited. The implications of research results regarding the influence of the platformecommerceand social media on the productivity of MSMEs in Palopo City shows that digital transformation is a crucial factor in increasing business competitiveness and efficiency.